Requirements for developing the roles of information specialists in public libraries in light of the transformation of the knowledge economy to achieve the goals of sustainable development - عاليه الهيف (المجلة الدولية لعلوم المكتبات والمعلومات)
The study aimed to highlight the role of the knowledge economy in achieving the goals of sustainable development for librarians and information specialists. Which requires a skilled workforce with many skills , competencies, ,proficiency in dealing with information and communication technologies and their cognitive applications; By identifying the information specialists' awareness of their role in the knowledge economy ,its impact to achieve the goals of sustainable development ,using the descriptive analytical survey method. The research was applied during the first semester of the academic year 2022-2023, 1443-1444. In knowledge economies, where approval was high in its repetitions. This can be explained in light of the Kingdom's tendencies towards knowledge-based economy,,through the programs of the Kingdom's Vision 2030, which comes the development of human resources in all sector , especially the information industry sectors, information specialists and libraries. There is also a need for more interest in offering non-stereotypical and continuous training related to “advanced programming skills”, “database and management skills”, “the ability to deal with artificial intelligence techniques ,use modern technologies , analyzing and producing systems for dealing with big data". The study recommended raising awareness of sustainable development for library workers so that libraries begin to be effective towards achieving the goals, while clarifying the role of libraries, including public libraries, in the sustainable development plan and directing the attention of those responsible for libraries to the pivotal role it plays. Information science specialists in the transformation of the knowledge economy society in achieving the goals of sustainable development.